Feeding habits of the Pacific Bluefin tuna (Thunnus orientalis) larvae in two nursery grounds based on morphological and metagenomic analyses. (May 2020) - Kodama, Taketoshi; Hirai, Junya; Tawa, Atsushi; Ishihara, Taiki; Ohshimo, Seiji
Abstract: The feeding ecology of Pacific Bluefin tuna (PBT: Thunnus orientalis ) larvae collected from two nursery grounds, namely the Japan Sea and the Nansei area (western North Pacific), was evaluated based on gut content analyses using morphological and metagenetic techniques. The PBT larvae were collected at the surface layer (≥30 m depth) in 2016 and 2017, and 172 and 114 individuals from the Japan Sea and Nansei area, respectively, were analyzed. A generalized additive model applied revealed that the number of prey in the gut increased with growth, in waters above 24 °C and in subsurface ( 30 m depth) waters, during daytime. The total dry weights of prey per gut calculated from the size of copepods and cladocerans also increased during daytime and with growth. Both the morphological and metagenetic analyses indicated that the taxonomic composition of gut contents was influenced by the food selectivity of PBT larvae and by zooplankton (prey) availability in the ambient water. Podonidae were positively selected as PBT larvae prey in both areas, and copepodites and adult Corycaeidae and Pontellidae were positively selected in the Nansei area only. A metagenetic approach indicated Calanidae copepods and soft zooplankton such as appendicularians as important preys in both areas. Other copepods were not positively selected using this approach, but Clausocalanidae and Oithonidae were frequently detected in the Japan Sea. This might be related to the higher abundances of these families in the Japan Sea than in the Nansei area. On the other hand, the cladoceran Penilia avirostris and the copepods Echinostomatidae and Oncaeidae were rarely observed in the guts of PBT larvae although were abundant in the water column. Overall, PBT larvae feed abundantly and grow fast in warm and long-day waters rich in Podonidae, Corycaeidae, Pontellidae, and larval copepods, which contributes to their survival and recruitment in the Japan Sea and Nansei area.